EKSPERIMENTASI MODEL CORE DENGAN CRT TERHADAP KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI SELF REGULATED LEARNING - Regina Cahya Tifanni; Yemi Kuswardi; Sutopo Sutopo (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
This research aims to determine the effect of implementing the CORE learning model with the CRT approach on problem-solving abilities from a self-regulated learning perspective. This study was conducted as a quasi-experimental method with a 2×3 factorial design. The population included all eighth-grade students of SMP Negeri 1 Semin in the 2025/2026 academic year, with 32 students from classes VIII D and VIII A selected using cluster random sampling. Data were obtained through problem-solving ability tests, SRL questionnaires, and documentation. Data analysis was performed using a two-way ANOVA with a significance level of 0.05. The results showed that implementing the CORE learning model with the CRT approach improved problem-solving abilities, the level of self-regulated learning had a positive effect on problem-solving abilities, and the effect of the learning model on problem-solving abilities was independent of self-regulated learning, and vice versa. The CORE learning model with the CRT approach can be implemented and modified using technology-based learning media to improve problem-solving abilities.